HUBUNGAN PELAYANAN KONSUMEN DAN FASILITAS PERUSAHAAN TERHADAP KEPUASAN KONSUMEN PADA PT. AVANT GUARD INDONESIA - RINOVIAN RAIS (SMART Management Journal, 2020)
The Purpose of this study was to determine the effect of customer service and company facilities on customer satisfaction at PT Avant Guard Indonesia and to determine the variables that have a greater influence between customer services and company facilities on customer satisfaction at PT Avant Guard Indonesia. Based on testing with Chi square (X²), it is found that there is a significant relationship between customer service and customer satisfaction, or the better the service provided, the better customer satisfiction, For the relationship between company facilities and customer satisfiction, it is found that there is a significant relationship between company facilities and customer satisfaction, or the better the company facilities provided, the better customer satisfaction. From the calculation, it is also known that service has a greater influence, so that that the second Hypothesis can be accepted.